Tension band wiring of fracture distal end of clavicle: Favorable clinical outcome among the patients - Kumar Chanda, Ashoke; Banerjee, Kallol; Mondal, Abhimanyu; Sarkar, Dipayan; Roy, Rajiv; Bank, Bivas (Asian Journal of Medical Sciences, 2023)
Background: A fracture of the clavicle is common traumatic injury. It can be classified into middle third, medial third, and distal third fractures. Around 10–15% of clavicle fractures occur in the distal third. The ideal method of fixation in distal third clavicle fracture remains controversial till date. Aims and Objectives: The clinical outcome of the patients having fracture of the distal end clavicle using rigid fixation with tension band wiring (TBW) with Kirshner wires and SS wire to be assessed instead of other conventional procedures. Materials and Methods: Eight patients of Neer type II closed distal-third clavicle fracture of <3 weeks of duration were included in our study. The fractures were reduced by open reduction and fixed with TBW with two K-wires and SS wire. Results: The mean average age of patients was 41.87 years. All fractures united clinically and radiologically. The mean average time of union was 12 weeks. There was two case of hardware prominence, no fracture related complications. One case of superficial infection was found in study. All of them regained near normal range of motion, and the mean average constant Murley score for distal clavicle fracture at the end of 1 year was 88. At the end of 1 year follow-up, all patients had reached their pre-injury performance levels. Conclusion: There was an encouraging result with TBW in distal third clavicle fracture in our study. This technique is simple with lesser need of expertise and is also cost effective.